Ferrocenyl amphiphilic block copolymer and supercapacitor as well as preparation method - CHANG XUEYI; CHENG ZHIYU; FAN HONGBO; NIU JUNFENG; QIU YONGFU (2018)
The invention discloses a ferrocenyl amphiphilic block copolymer and a supercapacitor as well as preparation method. The structural formula of the ferrocenyl amphiphilic block copolymer is described in the description. The ferrocenyl amphiphilic block copolymer provided by the invention has very good oxidation-reduction property and film forming property; the material can be used for developing the novel ferrocenyl pseudocapacitor. Based on electrochemical characteristics such as cyclic voltammetry and constant current charge-discharge, the pseudocapacitor is found to have the specific capacitance reaching up to 572.5F.g<-1> when current density is 5A.g<-1>; a PEO-PFc cycle life test is carried out under the condition of 50A.g<-1>, and a specific capacitance value is decreased by 23.8% after 3000 times of cycling, so that PEO-PFc is proved to be a good cathode material for the pseudocapacitor; therefore, a useful reference is provided for the development of the electrode material for the novel pseudocapacitor